Characterization of magnetic actuators by measuring of magnetic stray fields with GMR-sensors - Brela, Matthäus; Kassim, Najdet; Franke, Jörg (2013 3rd International Electric Drives Production Conference, EDPC 2013 - Proceedings, 2013)
Common defects in electromagnetic actuators due to manufacturing are heterogeneous magnetic properties of materials, cracks and defects in the flux guiding magnets and parasitic air gaps in and directly around the magnetic circuit. Considering the high cost pressure, test systems must adapt to the increasing complexity of the components and detect defects completely in-situ. For these requirements the novel and nondestructive measurement system is suitable to monitor and assure the quality of magnetic actuators within the manufacturing process. The measuring principle is based on the characterization of the magnetic circuit according to the magnetic stray fields that can be quantified by magnetoelectronic GMR-elements outside the circuit. GMR sensors are particularly suited due to their measurement range and their linearity. Their measurement range coincides with the magnetic stray fields which were demonstrated by magnetic field simulation of electromagnetic actuators. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electromagnetic actuators; GMR-sensor; magnetic stray fields; nondestructive measurement system

Fully automated rotor inspection apparatus with high flexibility for permanent magnet synchronous motors using an improved hall sensor line array - Meyer, Alexander Wilhelm; Heyder, Andreas; Brela, Matthäus; Urban, Nikolaus; Sparrer, Johannes; Franke, Jörg (5th International Conference on Electric Drives Production, EDPC 2015, 2015)
As a result of the market expansion of permanent magnet synchronous motors due to the increasing demand for high-performance drives for a wide range of applications such as traction drives for electric mobility, positioning drives for machine tools as well as high-precision drives for special-purpose machines and the quality demands involved, in-line capable measurement technology is needed. Thus in the area of electric drives manufacturing the rejection rate is required to be reduced by early fault detection. This can be achieved by measuring the rotor excitation field created by permanent magnets prior to the assembly of rotor and stator. In this Paper an apparatus for fully automated inspection of both internal and external rotors within a wide range of dimensions is presented. This is done with the aid of a one dimensional Hall-Sensor line array, which is manufactured with high accuracy and the use of an open source CNC system. The presented device is capable for in-line operation at the end of the rotor assembly process chain to detect possible magnetization and assembly faults prior to the final assembly of the electric drive by visualization of the rotor excitation field.

Hall measurement method for the detection of material defects in plastic-embedded permanent magnets of rotors - Brela, Matthäus; Michalski, Markus; Gebhardt, Hans Joerg; Franke, Jörg (IECON Proceedings (Industrial Electronics Conference), 2013)
The efficiency of electric drives is determined by the mechanical and magnetic properties of the functional elements, such as stator and rotor. Due to the electromagnetic interaction with the magnetic field, generated by the stator, the rotor transforms the magnetic energy into a rotational motion. It is characterized by its magnetization, its magnetic field strength, the field distribution and its geometric dimensions. The current challenge is to produce electrical drives with minimal loss. This requires ensuring the magnetic characteristics of the rotors. Errors that can occur during manufacture are cracks, blowholes or inclusions in the permanent magnet. Those can lead to commutation problems or to increased noise. For this purpose, a non-destructive and non-contact measurement method, based on the measurement of the magnetic field with Hall-effect sensors to detect defects in plastic-bonded permanent magnet rotors was developed. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Actuators and System Integration; Diagnostic and Prognostic; Fault Detection; Permanent Magnet Machines; Sensors

Laser Beam Melting Of NdFeB For The Production Of Rare-Earth Magnets - Kolb, Tobias; Urban, Nikolaus; Huber, Florian; Brela, Matthäus; Maurer, Dominik; Akbulut, Basri; Donocik, Christoph; Schmidt, Michael; Franke, Jörg (Proceedings of the 6th Electric Drives Production Conference, 2016)

Use of automated in-line capable magnetic stray field measurement method for monitoring the value chain quality of magnetic circuits - Brela, Matthäus; Heyder, Andreas; Dietlein, Fabian; Markert, Johannes; Franke, Jörg; Hauenstein, R.; Wagner, R. (2014 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2014, 2014)
Common defects in electromagnetic actuators due to the manufacturing process are heterogeneous magnetic properties of the materials, cracks and defects in the magnetic materials and parasitic air gaps in and directly around the magnetic circuit. In most cases the error cause can be found in the value chain and is caused by material handling, assembling tolerances, environmental influences, etc. Considering the high global cost pressure, test systems must be adapted to the increasing complexity of the components in order to be able to detect defects completely in-situ and have smallest possible amortization period. For these requirements the novel and nondestructive measurement system is suitable to monitor and assure quality of magnetic actuators within the manufacturing process. The measuring principle is the characterization of electromagnetic actuators according to the detection of magnetic stray fields outside the magnetic circuit and the magnetic useful field inside the actuator that can be quantified by magnetic sensors. The intensity of the magnetic stray fields depends on the magnetic flux density and flux distribution in the magnetic circuit. Permeability variations for example caused by air gaps or internal stresses influence the flux distribution. In most cases they are caused by process parameter variations of the manufacturing and assembling. With the developed method this influences can be detected in an early stage of the manufacturing process automatically and in-line. This can lead to more competitiveness and long-term viability of the location. © 2014 IEEE.
CRIS-Team Scopus Importer:2023-03-07